Biogeographical patterns and processes in the genus group Scotussae (Acrididae: Melanoplinae): an integrative approach - Scattolini, María Celeste (2020)
A biogeographical study of the genus group Scotussae, a clade of grasshoppers endemic to the subtropical temperate region of the La Plata Basin, South America, was performed within a phylogenetic context to test whether wing reduction reflects evolutionary and ecological processes within the clade. We used an integrative biogeographical approach to determine the role of geohistorical events, geography, ecology and phylogenetic niche conservatism on the distribution and diversification processes of the group. We performed a total evidence phylogenetic analysis and tested the phylogenetic signal of ecological niche traits (niche optimum and niche breadth). We also assessed the degree to which phylogenetic distance is correlated with geographical and ecological niche traits and we used BioGeoBEARS to estimate ancestral ranges. The results provided evidence for phylogenetic niche conservatism as well as a significant association between phylogeny and both geographical and, more strongly, ecological traits. Two main clades were clearly associated with wing development, and evidence points to the evolutionary and ecological processes within these two groups being different. The Brachypterous clade shows evidence that allopatric speciation was the main source of diversification, while for the Macropterous clade sympatric speciation seems more likely.